THE EMERGENCE OF MASS ATROCITY CONCEPTS: REFLECTIONS ON GENOCIDE, CRIMES AGAINST HUMANITY, WAR CRIMES AND ETHNIC CLEANSING - Whitehorn, Alan (Armenian Folia Anglistika, 2025)
The article commences with a brief listing of some of the key words and phrases used in journalistic accounts in the 1915 New York Times about the mass deportations and killings of ethnic Armenians in the Ottoman Empire. Exploring the emergence of academic and legal terms associated with such mass atrocities in general, a number of key concepts have been formulated, most notably war crimes, crimes against humanity, genocide and ethnic cleansing. Other suggested terms include democide, politicide, ethnocide, urbicide, gendercide and omnicide, which are also briefly discussed by way of background and overview. Amidst an analytical comparison of the meanings of the two terms ethnic cleansing and genocide, problematic aspects of using the term ethnic cleansing are raised and discussed. There has been a continuing global challenge of mass atrocity crimes, and today we witness increased usage of the problematic concept of ethnic cleansing in important, yet diverse case studies such as Nagorno-Karabakh and Gaza. It is suggested that other terms, such as war crimes, crimes against humanity and genocide, are more suitable terms, both analytically and morally.